Antioxidant Properties of Azadirachta Indica Leave Extracts - Hussain, Shabbir; Hafeez, Maleeha; Riaz, Muhammad; Massey, Shazma; Asghar, Amina; Javed, Atif (BioScientific Review, 2024)
Background: Azadirachta Indica is an important medicinal plant commonly found in India, Africa, America, Europe, and many other regions of the world. The current study was designed to investigate the concentrations of important phenolic/flavonoid contents of ethanolic extracts of Azadirachta Indica (neem) leaves (Lahore, Pakistan). Methods: High-performance liquid chromatography (HPLC) analysis revealed the presence of three phenolic compounds (gallic acid, sinapic acid, and caffeic acid) and two flavonols (Myricetin and Kaempferol). The plant extract contained the highest and lowest concentrations of myricetin acid (26.41µg/g) and kaempferol (3.35µg/g) among flavonols, respectively. Results: Both acids are helpful in the manufacturing of antioxidant medicines. Among phenolics, sinapic acid (45.73µg/g) and gallic acid (1.96µg/g) were present in highest and lowest concentrations in plant leaves, respectively. Conclusion: Gallic acid, sinapic acid, caffeic acid, myricetin, and kaempferol possess antioxidant and therapeutic potential and are highly beneficial for human health. Human beings can get many benefits and produce more medicines from the leaf extract of neem in the future. Many more advantages can also be taken from different parts of neem (leaves, seeds, and bark).